China's National Balance Sheet (2015): Leverage Adjustment and Risk Management - Li, Yang (Springer Singapore, 2018)
The book aims at perfecting the national governance system and improving national governance ability. It evaluates the balance sheets of the state and residents, non-financial corporations, financial institutions and the central bank, the central government, local government and external sectors - the goal being to provide a systematic analysis of the characteristics and trajectory of China's economic expansion and structural adjustment, as well as objective assessments of short and long-term economic operations, debt risks and financial risks with regard to the institutional and structural characteristics of economic development in market-oriented reform. It puts forward a preliminary analysis of China's national and sectoral balance sheets on the basis of scientific estimates of various kinds of data, analyzes from a new perspective the major issues that are currently troubling China - development sustainability, government transformation, local government debt, welfare reform, and the financial opening-up and stability - and explores corresponding policies, measures, and institutional arrangements. .